(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The learning process is perceived in the form of an optimal management object and an innovative approach to the optimal management of the process. The functional structure of the tutorial system "teacher-reader" is given, and on this basis the cyclical structure of calculation experience is created. Keywords: mathematical modeling, optimal control, didactic system, learning process, control object, program control, computational experiment, structure of functioning, functional structure.